2016
DOI: 10.3346/jkms.2016.31.11.1673
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Strain Typing ofMycobacterium tuberculosis: a Review of Frequently Used Methods

Abstract: Tuberculosis, caused by the bacterium Mycobacterium tuberculosis, remains one of the most serious global health problems. Molecular typing of M. tuberculosis has been used for various epidemiologic purposes as well as for clinical management. Currently, many techniques are available to type M. tuberculosis. Choosing the most appropriate technique in accordance with the existing laboratory conditions and the specific features of the geographic region is important. Insertion sequence IS6110-based restriction fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 93 publications
0
37
0
11
Order By: Relevance
“…The former occur throughout the genome in the form of direct repeats and insertion sequences, while the latter are a series of head-to-tail direct uninterrupted repeats in the form of variable number tandem repeats (VNTR). The most common techniques used to distinguish between the two mechanisms of TB recurrence include IS6110-restriction fragment length polymorphism (IS6110-RFLP) analysis, mycobacterial interspersed repetitive-unit variable number of tandem repeats (MIRU-VNTR) typing, and spacer oligonucleotide genotyping (spoligotyping) [4,23]. More recently, whole genome sequencing (WGS) has been used to compare strains representing different episodes of TB infection.…”
Section: Methodology Used To Study Recurrent Tbmentioning
confidence: 99%
“…The former occur throughout the genome in the form of direct repeats and insertion sequences, while the latter are a series of head-to-tail direct uninterrupted repeats in the form of variable number tandem repeats (VNTR). The most common techniques used to distinguish between the two mechanisms of TB recurrence include IS6110-restriction fragment length polymorphism (IS6110-RFLP) analysis, mycobacterial interspersed repetitive-unit variable number of tandem repeats (MIRU-VNTR) typing, and spacer oligonucleotide genotyping (spoligotyping) [4,23]. More recently, whole genome sequencing (WGS) has been used to compare strains representing different episodes of TB infection.…”
Section: Methodology Used To Study Recurrent Tbmentioning
confidence: 99%
“…In particular, some NTM species, especially MAC members, are frequently isolated from clinical laboratories. Molecular methods have also found wide application in the identification of mycobacteria in clinical specimens and at species level [14,15]. Koh, et al [16] in 2006, isolated NTMs from respiratory tract specimens which were defined mainly as MAC (48%) and M. abscessus (33%).…”
Section: Discussionmentioning
confidence: 99%
“…The rep-PCR lonae, 4.4% M. gordonae, 3.2% M. terrae, 1.8% M. scrofuloceum, 1.3% M. kansasii and M. szulgai [11]. In the study by Couto, et al [14], NTMs isolated from clinical samples [15] were identified mainly as follows 24.8% MAC, 15.4% M. gordonae, 9.4% M. fortuitum, 6.7% M chelonae, 6% M. xenopi, 4.7% M. peregrinum and 4% M. abscessus. In our study, 66.7% of cases were found to be M. tuberculosis by the rep-PCR method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite effective treatments, diagnostic and preventive measures that have become available in the last few decades. Molecular based typing techniques for the causative Mycobacterium tuberculosis (M. tuberculosis) complex have emerged as effective tools based on variation in insertion sequences and repetitive genomic sequences [1][2][3]. M. tuberculosis has a highly conserved genome containing useful markers that can be exploited in different typing techniques, such as those using Insertion Sequence IS6110 [4], Mycobacterial Interspersed Repetitive Units-Variable Number of Tandem Repeats (MIRU-VNTR) [5], Large Sequence Polymorphism (LSP) [6], Restriction Fragment Length Polymorphism (RFLP) [7] and reverse line dot blot spoligotyping [8,9].…”
Section: Introductionmentioning
confidence: 99%